Governing Children's Rights in Global Social Policy—International Organizations and the Thin Line Between Child Protection and Empowerment - Anna Holzscheiter (International Organizations in Global Social Governance, 2021)
This chapter locates children's rights in the context of global social governance. Social policy literature has hitherto neglected the centrality of child protection and children's rights to many key areas of social governance such as education and healthcare. The chapter traces the history of children's rights as a distinct sphere in international law from the first recognition of the special status of children, to the adoption of the UN Convention on the Rights of the Child (UNCRC), to the growth of the contemporary complex International Organization (IO) landscape. Children's rights enjoy growing visibility and relevance and continue to be a cross-cutting issue in international organizations of all kinds, making them a central dimension of global social governance. Nonetheless, the chapter highlights that the growth of the children's rights agenda has not been without conflict. International norms and measures surrounding children's rights continue to be challenged and questioned by scholars and practitioners alike. Furthermore, the analysis of children's rights provides opportunities to reconsider traditional approaches to global social policy.
Keywords: 300